Biocompatible Microrobots: Magnetically Actuated SiCN‐Based Ceramic Microrobot for Guided Cell Delivery (Adv. Healthcare Mater. 21/2019). Issue 21 (7th November 2019) - Gyak, Ki‐Won; Jeon, Sungwoong; Ha, Laura; Kim, Sangwon; Kim, Jin‐young; Lee, Kwang‐Sup; Choi, Hongsoo; Kim, Dong‐Pyo
Abstract : In article number 1900739 by Hongsoo Choi, Dong‐Pyo Kim, and co‐workers, biocompatible ceramic microrobots are developed for cell delivery for the first time. The microrobots are fabricated by 3D laser lithography, and magnetic nanoparticles are immobilized on the surface of the microrobots to manipulate the movement of the microrobots by an external magnetic field.